An Economic Evaluation of a Comprehensive School-Based Caries Prevention Program. (October 2019) - Huang, S.S.; Ruff, R.R.; Niederman, R.
Introduction: Current economic evaluations of school-based caries prevention programs (SCPPs) do not compare multiple types of SCPPs against each other and do not consider teeth beyond permanent first molars. Objectives: To assess the cost-effectiveness of a comprehensive SCPP relative to an SCPP focused on delivering sealants for permanent first molars only and to a default of no SCPP. Based on a societal perspective, a simulation model was used that compared the health and cost impacts on 1) permanent first molars only and 2) all posterior teeth. Methods: To calibrate the model, we used data from CariedAway, a comprehensive SCPP that used glass ionomer to prevent and arrest active decay among children. We then evaluated the incremental cost-effectiveness of implementing 3 alternate school-based approaches (comprehensive, sealant only, and no program) on only first molars and all posterior teeth. Probabilistic, 1-, and 2-way sensitivity analyses are included for robustness. Cost-effectiveness is assessed with a threshold of 54, 639 per averted disability-adjusted life year (DALY). Results: We first compared the 3 programs under the assumption of treating only first molars. This assessment indicated that CariedAway was less cost-effective than school-based sealant programs (SSPs): the resulting incremental cost-effectiveness ratio (ICER) for CariedAway versus SSPs was 283, 455 per averted DALY. However, when the model was extended to include CariedAway's treatment of all posterior teeth, CariedAway was not only cost-effective but also cost-saving relative to SSPs (ICER, –943, 460.88 per averted DALY; net cost, –261.45) and no SCPP (ICER, –400, 645.52 per averted DALY; net cost, –239.77). Conclusions: This study finds that economic evaluations assessing only cost and health impacts on permanent first molars may underestimate the cost-effectiveness of comprehensive SCPPs 1) preventing and arresting decay and 2) treating all teeth. Hence, there is an urgent need for economic evaluations of SCPPs to assess cost and health impacts across teeth beyond only permanent first molars. Knowledge Transfer Statement: The results of this study can be used by policy makers to understand how to evaluate economic evaluations of school-based caries prevention programs and what factors to consider when deciding on what types of programs to implement.